Patrimonio Cultural Inmaterial y Etnoturismo en la Parroquia Calpi del Cantón Riobamba. - Armas Bayas, Silvia Eliseth (2023)
Calpi is a rural parish in the Riobamba canton, in the province of Chimborazo. Its name means "Spider River", and it is an old town where several partialities or ayllus lived, such as the Calpi or Cápac. Its great variety of intangible heritage makes this community unique since intangible heritage not only refers to traditions inherited from the past, but also to contemporary rural and urban features of various cultural groups, which is why this research aims to determine the influence of the intangible cultural heritage with the ethnotourism of the Calpi parish of the Riobamba canton. The investigation is documentary through a qualitative research technique which is in charge of collecting and selecting information from written documents. A field investigation was carried out in order to apply the appropriate surveys and data and information collection to have an adequate and valuable investigation for new researchers, it is of a correlational nature in knowing the relationship that exists between two variables, that is, the independent variable (intangible cultural heritage) and the dependent variable (etnoturismo) in the Calpi Parish, through the study of these variables it was possible to determine that in the Calpi parish, the intangible cultural heritage has an influence on ethnotourism since it is conducive to the greater influx of tourists to the parish, since there are customs and traditions unique to the place.